PENGGUNAAN BAHASA SANTUN - Alimuddin L (Program Studi Administrasi Publik, 2014)
This paper describes the use of linguistic politeness in children’s speech. This data was obtained through aqualitative approach with the aim of explaining the facts contained in linguistic politeness. The results obtained in this research are the forms of linguistic politeness including statement, question, command, prohibition, demand, and greeting. Besides that, there are alsocommunicative functions which consist of reprimand, comment, curiosities, request permission, pleasing, and informative. In addition, the use of the word containing the value of the most widely used honorifics as politeness signifier of children.